Effect of red betel (Piper crocatum Ruiz and Pav) leaves extract on blood glucose levels and ankle brachial pressure index (ABPI) among patients with type 2 diabetes mellitus - Wigatiningtyas, Bios Cendekia; Ta'adi, Ta'adi; Walin, Walin (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Hyperglycemia often occurs in DM patients even though they have received pharmacological therapy, thus encouraging people to consume herbal medicines. The dosage of herbal therapy consumed by the community is not appropriate, only the dosage of community assumptions, resulting in negative impacts. Chronic hyperglycemia causes worsening of the Ankle Brachial Pressure Index (ABPI) score. Giving red betel extract with the right dose can be a solution, because red betel extract contains flavonoids that can inhibit y-amylase and y-glucosidase so that the body can control blood sugar levels and improve ABPI scores. Purpose: To determine effectiveness of red betel extract on fasting blood sugar levels and ABPI. Method: A quasy experiment approach, specially focusing on pretest and posttest group. The study took place from October-November 2024, in Padangsari and Srondol Health Centers, Semarang. The independent variable was red betel leaf extractthe dependent variables is fasting blood sugar levels and ABPI. Using purposive sampling and Lemeshow formula, 70 respondents were selected which were divided into 2 groups, who met specific inclusion and exclusion criteria. Analysis proceeded with a univariate test to determine the frequency distribution of respondent’s characteristics, followed by bivariate analysis using man whitney test. Results: Red betel leaf extract significantly reduced blood sugar levels in patients with type 2 diabetes mellitus with an intervention value of 112.83 ± 15.227 compared to control of 191.46 ± 72277 with a large Cohen's d effect of 0.87 and increased the value of the Ankle Brachial Pressure Index or ABPI in the intervention group by 0.855 ± 0.045 compared to control by 0.674 ± 0.094 with a large d effect of 1.22 These findings suggest that red beet extract has potential as an adjuvant therapy in glycemic control and improvement of peripheral circulation. Conclusion: Betel leaf extract has been shown to be effective in reducing fasting blood sugar levels and improving Ankle Brachial Pressure Index (ABPI) scores in patients with type II diabetes mellitus.